Saat Usia Jadi Batas: Kepastian Hukum dalam Aturan Pensiun - Christina, Leona Flentje; Hufron (Journal Evidence Of Law, 2025)
The objective of this study is to analyze the regulatory aspects of the retirement age limit for workers in Indonesia by examining the existing legal framework from a juridical perspective, particularly in relation to legal certainty based on the normative structure of prevailing laws and regulations. Although numerous studies have been conducted on retirement age, most of them focus primarily on the fulfillment of workers' rights after retirement. This study specifically concentrates on the legal basis for determining the retirement age, especially in situations where such provisions are not stipulated in the Company Regulations (CR) or Collective Labor Agreements (CLA). These provisions serve as normative instruments that function as the legal foundation for the implementation of employment relationships. The study adopts a case study approach, analyzed through the lens of the legal certainty theory. To strengthen the analytical framework, supporting concepts such as retirement and termination of employment are also discussed. The combination of these theories and concepts aims to establish a normative foundation for formulating retirement age policies that provide legal certainty for workers. The absence of explicit regulations regarding retirement age in the Labor Law has the potential to create legal uncertainty. Therefore, a clear stipulation of the retirement age is a crucial instrument to enhance legal protection, ensure industrial relations stability, and minimize labor disputes.